Double Negative T Cell Proportion of CD3+ Cells Present in the Thyroid Microenvironment is an Immunogenomic Marker for Predicting Thyroid Cancer - Richard, Brennon (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF To see the formatted meeting abstract.